Students' perceived satisfaction level of the Nanyang Technological University library. - Lim, Jeannette Mui Ling. (2008)
The objective of this Applied Research Project is to investigate students’ perceived satisfaction of the Nanyang Technological University (NTU) Library. To do that, we examined two important areas of the Library. These are current services and printed materials that are provided by the Library.